A high throughput tensile ice adhesion measurement system. (October 2020) - Mirshahidi, Kiana; Alasvand Zarasvand, Kamran; Luo, Wenting; Golovin, Kevin
Graphical abstract: Abstract: A prerequisite for designing materials with low adhesion to ice is to accurately measure the ice adhesion strength of the surface. The majority of studies in this field have typically focused on manipulating and measuring the adhesion strength of different materials under shear stress. Among them, elastomers have proven to be promising ice-phobic surfaces because they enable interfacial cavitation, a tension-driven surface instability. In this work, a high throughput, low cost device is designed to measure the tensile ice adhesion strength of different surfaces. The design and construction of the tensile ice adhesion measurement system is presented, along with the reasoning for the design decisions. The performance of the setup is characterized using experimental trials varying parameters such as temperature, pull-off speed, thickness of the substrate, and ice/substrate interfacial area, to verify the precision of the measurements.